2002
DOI: 10.1111/j.1349-7006.2002.tb02473.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐sensitive Ovarian Carcinoma Cell Line (OvBH‐1)

Abstract: OvBH-1 cells from a patient with ovarian clear cell carcinoma were established and their biochemical status was analyzed. Cells grown at 37°C exhibited normal cell cycle distribution, whereas the cells shifted to 31°C were arrested in the G 2 /M phase of the cell cycle. Immunochemical analysis using anti-p53 antibodies (DO-1, PAb240, PAb421, and PAb1620) revealed that only the DO-1 antibody reacted with p53 with a high and similar percentage at both temperatures. PAb240 reacted with a low percentage of cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Based on published data, it can be assumed that only the cell clones with unique stemness features were selected during the immortalization procedure [26,27]. This suggestion might be confirmed by the high nuclear accumulation of the p53 protein found in the majority of immortalized cells, which indicated that only malignant cells were able to survive and proliferate [7]. Strong p53 immunopositivity in immortalized cells found in the current study indicates that the selection of cells carried the TP53 gene mutation, similar to the published data on the correlation between p53 overexpression and gene mutation [28][29][30].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on published data, it can be assumed that only the cell clones with unique stemness features were selected during the immortalization procedure [26,27]. This suggestion might be confirmed by the high nuclear accumulation of the p53 protein found in the majority of immortalized cells, which indicated that only malignant cells were able to survive and proliferate [7]. Strong p53 immunopositivity in immortalized cells found in the current study indicates that the selection of cells carried the TP53 gene mutation, similar to the published data on the correlation between p53 overexpression and gene mutation [28][29][30].…”
Section: Discussionmentioning
confidence: 97%
“…One such procedure is spontaneous immortalization, which occurs during the numerous passages of primary cells (hundreds of cell passages). An example of spontaneous immortalization is the ovarian cancer OvBH-1 cell line derived from the ascitic fluid of a patient with an ovarian clear-cell adenocarcinoma [7] and a high-grade serous ovarian cancer cell line OVPA8 [8]. Another way to obtain a cell line is to immortalize the cells using vectors carrying telomerase or Simian virus 40 (SV40) genes.…”
Section: Introductionmentioning
confidence: 99%
“…We found that both cell lines expressed high levels of p53 indicating a stabilization and inactivation of the protein. In the case of OvBH-1 cells this stabilization is not due to a mutation in the p53 gene because sequence analysis revealed only a neutral genetic polymorphism (17,39). OV-MZ-32 cells express a p53 mutant with a deletion between amino acids 314 and 318 (15).…”
Section: Discussionmentioning
confidence: 99%
“…OV-MZ-32 cells carry a 13-bp deletion from codon 314 to codon 318 of the p53 gene. OvBH-1 is a temperature-sensitive ovarian clear cell carcinoma cell line, characterized in detail elsewhere (16,17). Polish Patent Nr.…”
Section: Methodsmentioning
confidence: 99%
“…The OptiMEM GlutaMax medium was supplemented with 3% FBS and a 1% penicillin/streptomycin solution. Tumor cells from the ascitic fluid were isolated according to the protocol described by [57]. Briefly, the ascitic fluid was centrifuged at 1000× g for 10 min.…”
Section: Isolation and Characterization Of Human Primary Ovarian Canc...mentioning
confidence: 99%